Resident Training in Transitioning Youth With Epilepsy Into Adult Care. (January 2021) - Tirol, Francis G.; Kumar, Anagha
Objective: To appraise the current training of Neurology (N), Pediatric (P), and Med-Peds (MP) residents at MedStar Georgetown University Hospital (MGUH) in providing care to patients with epilepsy who are transitioning from pediatric to adult care. Methods: Through an online questionnaire, we surveyed Neurology, Pediatric, and Med-Peds residents to assess their knowledge, confidence, and experience at transitioning youth with epilepsy to adult-oriented health care. Results: N, P, and MP residents generally rated their knowledge and confidence at providing transition care to youth with epilepsy to be poor; however, P and MP residents rated higher in limited measures of knowledge and experience. Conclusion: Our appraisal of resident training in transitions care for youth with epilepsy has highlighted training elements in our institution that require attention for both adult and pediatric providers, leading to the formulation of an educational intervention that will promote experiential and multimodal approaches in this area.